Study on Efficient Electrode from Electronic waste renewed carbon material for sodium battery applications. Issue 2 (April 2021) - Arjunan, P.; Kouthaman, M.; Kannan, K.; Diwakar, K.; Priyanka, V.; Subadevi, R.; Sivakumar, M.
Abstract: The present work enlightens the preparation of anode material for sodium battery by utilizing the powder from exhausted printer cartridges (pEPC). Herein, the toner powder was heat treated to obtain carbon-ferric (C/Fe3 O4 ) composite. The obtained composite's structure, surface morphology were analyzed using X-ray diffraction, and electron microscopic analyses. The electrochemical performance of composite material was examined by using this material as anode for sodium ion battery. The composite material delivered an initial discharge capacity of 410 m Ah g −1 in the range 0.1–3.0 V with 93% coulombic efficiency; Even after 100 cycles, the material delivered 280 m Ah g −1 . This work proposes the potentiality of recycling the waste toner as anode materials for sodium ion batteries. By this way, the environmental issues can be minimized from the hazardous e-waste and renewed it for energy storage application. Graphical Abstract: ga1 Highlights: This work reveals the potentiality of recycled hazardous electronic waste. Toner powders from e-waste applied in synthesizing electrode for Na-battery. The e-waste based composite material delivered a capacity of 410 m Ah g −1 at 0.1 C. This eco-friendly anode material holds a long life span.